Decarbonising Economies - Bulkeley, Harriet (Physical Sciences, 2022)
Decarbonising Economies analyses the ways in which questions of agency, power, geography and materiality shape the conditions of possibility for a low carbon future. This title is also available as Open Access on Cambridge Core.